Peningkatan keterampilan speaking mahasiswa tadris bahasa inggris melalui pembelajaran blended learning - Nada, Salwa Zanuba Qotrun (Maliki Interdisciplinary Journal, 2025)
This study aims to explore the impact of implementing the blended learning method on enhancing the speaking skills of students in the English Education program. The methodology employed is a systematic literature review, which involves searching and analyzing various academic sources, including journals, scholarly articles, theses, dissertations, and relevant e-books. The findings indicate that blended learning, which combines face-to-face instruction with online learning, significantly improves students’ speaking abilities. Results demonstrate that this learning model not only enhances speaking skills but also boosts students’ confidence and motivation in communicating in English. By utilizing e-learning platforms such as Google Classroom and Edmodo, students have opportunities for independent practice and receive direct feedback from instructors. This research recommends that educational institutions continue to implement blended learning methods to create more interactive and effective learning experiences.